Integrative redescription of Hypsibius pallidoides Pilato et al., 2011 (Eutardigrada: Hypsibioidea) with the erection of a new genus and discussion on the phylogeny of Hypsibiidae - Tumanov, Denis V. (European Journal of Taxonomy, 2020)
An integrative redescription of Hypsibius pallidoides Pilato, Kiosya, Lisi, Inshina & Biserov, 2011 was undertaken following a reexamination of the type material and new material using high-quality light microscopy, scanning electron microscopy and methods of molecular taxonomy. Detailed morphological investigations revealed a unique complex of characters that precluded the attribution of this species to the genus Hypsibius Ehrenberg, 1848. Furthermore, phylogenetic analyses indicated the affinity of this species within the subfamily Pilatobiinae (Hypsibiidae). Notahypsibius gen. nov. is erected for H. pallidoides and two putatively related species: H. scaber Maucci, 1987 and Ramazzottius arcticus (Murray, 1907). An emended diagnosis for the genus Pilatobius is given, while the subfamily Pilatobiinae lacks a cohesive morphological diagnosis despite representing, at the same time, a well-supported molecular clade. Obvious controversy between the results of the morphological and molecular analyses of the phylogeny of Hypsibioidea is discussed. The distribution of morphological characters such as the claw type, organization of the bucco-pharyngeal apparatus, and egg shell sculpture type within Eutardigrada is analyzed and their phylogenetic significance discussed.